Evaluating physical fitness and the relationship between field and non-field tests in male rugby academy players based on playing position - Joannides, B.; Ireland, M. G.; Ras, J.; Leach, L. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Rugby is a globally played sport with statistically significant variance in the physical fitness levels of rugby players in different playing positions. The aim of the study was to evaluate the physical fitness levels in rugby academy players and to determine the relationship between non-field and field tests based on the forward and backline playing positions. METHODS: The study made use of cross-sectional, secondary data and employed a quantitative and correlational research design. Forty-five rugby academy players from a rugby academy in the Western Province were conveniently recruited for the study and split into forward and backline playing positions. The non-field tests were stature, body mass, and body fat percentage, bench-press, pull-ups, and vertical jump, while the field tests were the10-m, 30-m, and 40-m sprints, the Broncho Test, and the repeat sprintability test. Data analysis comprised independent samples t-test, Pearson`s correlation, and linear and logistic regression analysis. The level of statistical significance was set at P<0.05. RESULTS: Forwards were significantly heavier, stronger and more powerful than backline players (P<0.05). Backline players had a lower body fat percentage, were faster, and had a higher anaerobic endurance capacity, and higher muscular endurance (P<0.05). Body mass, body fat percentage, aerobic capacity, absolute muscular power, and relative muscular strength were all significant predictors of speed (P<0.01), and body mass was a significant predictor of anaerobic capacity (P<0.05). CONCLUSIONS: Forwards had higher absolute muscular strength and peak power output, whereas backs were significantly lighter, faster, relatively stronger, and possessed higher muscular endurance and were significantly influenced, in particular, by body composition and aerobic capacity.